2005
DOI: 10.1157/13076608
|View full text |Cite
|
Sign up to set email alerts
|

Percepción de la demanda y necesidades de formación en salud mental de los médicos de atención primaria

Abstract: In opinion of most of the physicians the mental disorders are related with, at least, 1 of each 5 consultations. A high proportion considers that the teams of PHC cannot be taken charge of the existent demand, mainly when it is high the assistance pressure. Most says that more specific training should exist in MH and more coordination with the specialized services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
6
0
5
Order By: Relevance
“…Esta discordancia podría deberse a la estigmatización que todavía rodea a la patología mental 15 , que genera rechazo hacia el reconocimiento de estos diagnósticos por los propios pacientes. Es improbable que las diferencias se deban al sobrediagnóstico en atención primaria, por la complejidad de la detección de estos trastornos 16 . El estudio ESEMed-España 17 detectó que un 8,4% de los españoles había presentado un trastorno mental durante el último año, con mayor prevalencia en las mujeres, y estos resultados son inferiores a los observados en las ENS y mucho menores que en la HCE.…”
Section: Discussionunclassified
“…Esta discordancia podría deberse a la estigmatización que todavía rodea a la patología mental 15 , que genera rechazo hacia el reconocimiento de estos diagnósticos por los propios pacientes. Es improbable que las diferencias se deban al sobrediagnóstico en atención primaria, por la complejidad de la detección de estos trastornos 16 . El estudio ESEMed-España 17 detectó que un 8,4% de los españoles había presentado un trastorno mental durante el último año, con mayor prevalencia en las mujeres, y estos resultados son inferiores a los observados en las ENS y mucho menores que en la HCE.…”
Section: Discussionunclassified
“…Several reports have demonstrated that insufficient human resources in Spain can lead to misdiagnosis and malpractice [18,19]; moreover, this deficit of trained staff places increased demands on an already oversaturated health care system. Despite this lack of resources, several Spanish studies have found that CBT group therapy is highly efficacious in treating depression in both the short and long term [57], as well as for other EDs [58].…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, the diagnosis of an ED is usually first made by the GP who must decide, in a very brief consultation (ie, less than 7 minutes), which psychoactive drugs to prescribe (if any) and whether or not the patient needs specialized care [18]. As a result of these time constraints, the most common treatments are pharmacological interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, patients with emotional disorders like PD are assessed by their GP who, after only a brief consultation, must decide whether specialized care is required or not [ 16 ]. To facilitate this decision-making process for the GP, adequate screening tools with good psychometric properties are needed to identify patients who are candidates for referral (positive screening test result) to a specialized service (psychological or psychiatric treatment).…”
Section: Discussionmentioning
confidence: 99%